Preliminary geological map of the AC-H-1 quadrangle- an integrated mapping study usind Dawn spacecraft data - Ruesch, Ottaviano; McFadden, Lucy A.; Hiesinger, Harald; Scully, J.E.C.; Kneissl, T.; Kynan, H.G.; Williams, David; Roatsch, Thomas; Preusker, Frank (2015)
We present a photo-geological map of the “Asari” quadrangle covering the North Pole area of Ceres (66°N-90°N), based on Dawn Framing Camera images and mosaics with a resolution of ~400 m/pixel. The mapping process is supported by a stereo- photogrammetric digital elevation model. We identified few isolated plateaus of up to ~5 km in altitude relative to the datum and topographic depressions interpreted to be highly degraded impact basins. At 85°N/8°E a cone-shaped positive relief is found, few te of kms large. Overall, the entire quadrangle is heavily cratered, and our measurements of crater density (9.8E-04 km-2 for crater diameters >10 km) identify the area as the most cratered on Ceres. This suggest a different geological history of the quadrangle relative to, e.g., the equatorial regions. The morphology of impact craters is characterized by central peaks and mass wasting deposits. We identified a morphologically-fresh mass wasting deposit at 78°N/38°E, 20 km in length, with a lobate margin and striations on its surface. This deposit and the positive relief at 85°N/8°E will be the focus of future investigations when higher spatia resolution images will be acquired by the Dawn Framing Camera. Observations with a spatial resolution of up to 35 m/pixel are planned and will allow photo-geological mapping at higher details. Support by N. Schmedemann, S. Marchi, R. Jaumann, A. Nathue C.A. Raymond, C.T. Russell, and the Dawn Instrument, Operations, and Science Teams is acknowledged.